LA PROTESTA ESTUDIANTIL EN CHILE. - Aigneren, Miguel (La Sociología en sus Escenarios, 2012)
Abstract. It was developed in the Chile of 2011, a new social process: the social protest that heads the Chilean students who have managed to install the necessity of a deep change in Chile. One has taken place what until recently it was considered impossible: that a clear majority shares the idea that economic, social, institutional and cultural the model that restored the military dictatorship and that was guaranteed by twenty years of government of the Concertacion must be modified until in its roots open passage to social justice. This demand by the change, from the exigency of equality of rights in the education, cradle in one based denunciation of the inequality and discrimination that suffers vast sectors of Chileans in education, health, house, wages, etc., has taken place in a praised country of Latin America like example by its model of market economy. The students have been asking themselves, if for forty years, when the country was poorer, the education was gratuitous, what has passed with the development and the high indices of growth? , where it is the money of the progress? If the mobilizations have been so strong it also must to the unjust thing of the Chilean educational model, implanted by the dictatorship and developed by the civil governments happened who it. A stage of the history of the country is finishing. One began more ago than twenty years and has included five governments. It began full of hopes when the Chileans put aim in 1988 to a dictatorship. Beyond its profits, the postdictatorial stage accumulated hopelessness and frustration. The realised promises have not consolidated a deeply unjust society. Resumen. Se gestó en Chile de 2011, un proceso social nuevo: la protesta social que encabezan los estudiantes chilenos que ha logrado instalar la necesidad de un cambio profundo en Chile. Se ha producido lo que hasta hace poco se consideraba imposible: que una clara mayoría comparta la idea de que el modelo económico, social, institucional y cultural que instauró la dictadura militar y que fue avalado por veinte años de gobierno de la Concertación tiene que ser modificado hasta en sus raíces para abrir paso a la justicia social. Esta demanda por el cambio, a partir de la exigencia de igualdad de derechos en la educación, basada en una fundamentada denuncia de la desigualdad y discriminación que padece vastos sectores de chilenos en educación, salud, vivienda, salarios, etc., se ha producido en un país de América Latina alabado como ejemplo por su modelo de economía de mercado. Se preguntan los estudiantes, si hace cuarenta años, cuando el país era más pobre, la educación era gratuita, ¿qué ha pasado con el desarrollo y los altos índices de crecimiento?, ¿dónde está el dinero del progreso? Si las movilizaciones han sido tan fuertes se debe también a lo injusto del modelo educacional chileno, implantado por la dictadura y desarrollado por los gobiernos civiles que la sucedieron.Está terminando una etapa de la historia del país. Se inició hace más de veinte años y ha abarcado cinco gobiernos. Comenzó llena de esperanzas cuando los chilenos pusieron fin en 1988 a una dictadura. Más allá de sus logros, la etapa postdictatorial acumuló desesperanza y frustración. Las promesas no realizadas han consolidado una sociedad profundamente injusta.